Nonalcoholic fatty liver disease is specifically related to the risk of hepatocellular cancer but not extrahepatic malignancies - Albhaisi, Somaya; McClish, Donna; Kang, Le; Gal, Tamas; Sanyal, Arun J. (Frontiers in Endocrinology, 2022)
OBJECTIVE: We performed a matched cohort study among individuals with and without non-alcoholic fatty liver disease (NAFLD) to determine: (1) the incidence of cancers (extrahepatic and liver) and their spectrum, and (2) if NAFLD increases risk of extrahepatic cancers. METHODS: The NAFLD and non-NAFLD (control) cohorts were identified from electronic medical records via International Classification of Diseases (ICD) codes from a single center and followed from 2010-2019. Cohorts were matched 1:2 for age, sex, race, body mass index (BMI) and type 2 diabetes. RESULTS: A total of 1412 subjects were included for the analyses. There were 477 individuals with NAFLD and 935 controls (median age: 52 years, female: 54%, white vs black: 59% vs 38%, median BMI: 30.4 kg/m2, Type 2 diabetes: 34%). The cancer incidence (per 100,000-person years) was 535 vs 1513 (NAFLD vs control). Liver cancer incidence (per 100,000-person years) was 89 in NAFLD vs 0 in control group, whereas the incidence of malignancy was higher across other types of cancer in control versus NAFLD group. CONCLUSIONS: The overall extrahepatic cancer risk in NAFLD is not increased above and beyond the risk from background risk factors such as age, race, sex, BMI and type 2 diabetes.